2019
DOI: 10.5696/2156-9614-9.24.191208
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Performance and Economic Growth in Middle East and North Africa Countries

Abstract: Background.Studies on environmental performance/quality and economic growth show inconclusive results.Objective.The aim of the present study is to assess the non-linear relationship between environmental performance and economic growth in the Middle East and North Africa (MENA) region from 2002–2018.Methods.A sample of fourteen (14) MENA countries was used in the present analysis. However, due to important differences between countries in this region, the whole sample was divided into two sub-samples; nine Mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Cross-country comparisons were used on the individual determinants of environmental performance. First, it concerns the impact of corruption (Sekrafi & Sghaier, 2018), development of democracy (Winslow, 2005;Fredriksson & Neumayer, 2013), public governance (Handoyo & Fitriyah, 2019;Basrija & Handoyo, 2019), and the GDP (Dinda, 2004;Dkhili, 2019;Gorham et al, 2019). It was found that corruption is strongly associated with high emissions of CO2 and environmental degradation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-country comparisons were used on the individual determinants of environmental performance. First, it concerns the impact of corruption (Sekrafi & Sghaier, 2018), development of democracy (Winslow, 2005;Fredriksson & Neumayer, 2013), public governance (Handoyo & Fitriyah, 2019;Basrija & Handoyo, 2019), and the GDP (Dinda, 2004;Dkhili, 2019;Gorham et al, 2019). It was found that corruption is strongly associated with high emissions of CO2 and environmental degradation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical studies of the relationship between environmental performance and the Gross Domestic Product (GDP) have shown inconsistent results. Іt is often argued that the relationship between the GDP and environmental performance is described by the Environmental Kuznets Curve (Gozgor, 2017;Irdhad & Hussain, 2017;Dkhili, 2019). It has an inverted U-shape, which means environmental degradation with an increase in GDP at an early stage of economic development and a reversal of the trend after reaching a certain threshold.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Managing a balance between ensuring the growth and development of a nation and the maintenance of the environment to ensure a balanced ecosystem is an issue most economies have to grapple with. Environmental sustainability refers to the long-term preservation of valuable natural resources within a developing human context (Dkhili, 2019). While sustainability is a characteristic of dynamic systems that self-maintain over time, it is not a predefined endpoint.…”
Section: Introductionmentioning
confidence: 99%